The Manager’ Perceptions Towards The Quality Management System (Qms) In Iso/Cd2 9001:2000 - Wan Salleh, W.Muhd Rahimi (2000)

(untitled)
The quality management system (QMS) standard is the revised version of the 1994 quality system (QS) standard. It prescribes the minimum requirements of implementing the quality system in an organisation. In lieu with the development of modem business management philosophy and practices, the standards are periodically reviewed.